The relation between strength and power in professional rugby league players - Baker, D.; Nance, S. (The Journal of Strength and Conditioning Research, 1999)
The purpose of this investigation was to analyze the relation between measures of maximal strength and maximal power generated during exercises with similar movement patterns. Twenty professional rugby league players were examined for maximal strength in a 3 repetition maximum (RM) full squat and 3RM bench press exercise and for maximal power during a jump squat and incline bench press throw exercise. A 3RM power clean from the hang was also examined to determine if this exercise was related to lower or upper strength and power. The results indicate that maximal strength is highly related to maximal power in all the tests performed (r = 0.55-0.89, p 0.05). The power clean from the hang is related more to lower-body squat strength and jump squat power (r = 0.79) than to upper-body bench press strength or incline bench throw power (r = 0.51-0.55). The practical application of this data suggests that while strength and power are highly related, a large degree of variance still exists. This may imply that further specific power training may be warranted to maximize power development, especially for the upper body.